PERANAN DESA ADAT PECATU DALAM PELESTARIAN DAYA TARIK WISATA PURA ULUWATU DI KABUPATEN BADUNG - Wigantara, Agus; Suryasih, Ida Ayu (JURNAL DESTINASI PARIWISATA; Vol 2 No 2 (2014): VOL 2, NO 2 (2014): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2014.v02.i02.p08, 2014)
ABSTRACT The Research raised the title "The Role of Indigenous Pecatu village in the tourist attraction in Badung regency." This study aims to allow the reader to get an overview of the role of traditional village in the preservation of tourist attractions Pura Uluwatu, and readers also get donations the idea that there are shortcomings in the preservation of tourist attractions Pura Uluwatu. Problems are taken in this paper regarding the role of Indigenous Village Pecatu How the Preservation of tourist attraction Uluwatu Temple in Badung and Is Managed Objects and attractions in the Pura Desa Adat Pecatu Uluwatu by've been able to realize Preservation. With the problems that exist here the authors find data as complete to be able to achieve the goals which aim to identify the role of the traditional village of Pecatu Institute in Preservation tourist attraction Uluwatu Temple in Badung regency and Managed Objects and Knowing Travel Attractions in Uluwatu by Desa Adat Pecatu been able to realize the preservation or even slow him down The data used in this study Desa Adat Pecatu role in the business object that can be seen in the form of the development of tourist attractions, Accessibility and facilities in the area of ??Pura Uluwatu. The data obtained through observation, interviews, and questionnaires. In analyzing the data used method of qualitative analysis is to outline the state of the object of study in detail through the sentence. In this report, also submitted suggestions based on discussions that have been compiled and refers to the direction of future development better.
Keywords: Role, Preservation, tourist attraction dan indigenous village